Collateral nuclease activity of TnpB triggered by high temperature enables fast and sensitive nucleic acid detection - Ying Xu; Wen Yin; Yibin Cheng; Wei Zeng; Wenqiang Li; Wanping Chen; Fei Wang; Nan Peng; Lixin Ma; Tao Liu (Communications Biology)
Abstract TnpB proteins encoded in the IS200/IS605 family are RNA-guided endonuclease which can be harnessed in genome editing. However, the collateral nuclease activity of TnpB remains poorly understood, which limits the development of TnpB-based diagnostic tools. Here we showed that TnpB from a thermophilic archaeon exhibits enhanced collateral ssDNA cleavage activity (trans-cleavage) activated by high temperature. Mutations either in the TAM or seed sequences of the target DNA impair the trans-cleavage activity, which indicates its potential to be employed in molecular diagnostic. Importantly, by optimizing the length and the sequences of the collateral substrates, we have developed a new nucleic acid detection method based on TnpB with a sensitivity of 29 cp μl−1 in 30 min, which we name it TESD (TnpB Enable fast and Sensitive Detection). In summary, our findings illustrate the collateral nuclease activity of a TnpB from thermophiles and provide a novel platform for molecular diagnostics.